IMPLEMENTASI PENDAFTARAN HAK ATAS TANAH MELALUI PROYEK AJUDIKASI ( Studi di Wilayah Kerja Kantor Pertanahan Kabupaten Kutai Kartanegara ) - Simeon Palinggi (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTThe registration of land rights through adjudication project in West Kutai, in practice it is straightforward and easy registration. Where the location has been determined based on the criteria in the decision of the Minister of Agrarian Affairs No.. 3 1995 where the location tersebur evidence possessed little or land still has not been registered by their owners, land registration through adjudication is more effective than sporadic land registration done by landowner sendiri.Untuk in West Kutai project through the implementation of Registration of land adjudication have reached the target of 10,000 in the field because of the West Kutai District Adjudication land registration project through appropriate Government Regulation No.24 of 1997 and Article 19 of the BAL has been achieved, namely legal certainty of the existence of each certificate as evidence.